Access of youth agripreneurs to agricultural finance for entrepreneurship and self-employment in Mali and Senegal - CGIAR Research Program on Rice (2021)
Within the PEJERIZ (Promoting youth entrepreneurship and job creation in West Africa’s rice value chain) project, two national agricultural banks in Mali (BNDA) and Senegal (La Banque Agricole) have accepted to sign agreements with AfricaRice to finance for the first time youth enterprises.